Enzyme Engineering: Current Trends and Future Perspectives. Issue 2 (17th February 2021) - Sharma, Anshula; Gupta, Gaganjot; Ahmad, Tawseef; Mansoor, Sheikh; Kaur, Baljinder
ABSTRACT: Enzyme-based biocatalysts have a wide range of industrial applications for production, processing and improving the quality attributes of animal feed, beverages, detergent, food, pharmaceutical and textile products. Microorganisms are the major sources of enzymes but natural enzymes as biocatalysts have limitations such as lower catalytic efficiency at ambient conditions, enzyme denaturation due to inability to withstand the pressure of large-scale industrial fermenters and poor productivity in native microbial cultures. Therefore, to meet their increasing demand at the industrial level, native enzymes are often engineered to work under nonphysiological reactions, to design innovative and efficient enzyme catalyzed pathways, and for the production of novel metabolites. Commonly employed enzyme engineering strategies include directed evolution, site-directed mutagenesis, truncation, and terminal fusion. These powerful and revolutionary techniques of enzyme engineering provide excellent opportunities for tailoring existing enzymes and constructing highly efficient novel industrial enzymes for the cost-effective production of value-added products. The present review highlights the major enzyme engineering strategies and methods to modify and optimize key catalytic properties, structure stabilization and introducing novel features to cater growing requirement of enzyme regulated industrial bioprocesses.